Synergistic enhancement of microwave absorption in CNT-NZF-CI/epoxy and carbon black/epoxy nanocomposites through dual-phase structuring - Idza Riati Ibrahim; Rodziah Nazlan; Siti Nor Ain Rusly; Fadzidah Mohd Idris; Khamirul Amin Matori; Ismayadi Ismail; Ghazaleh Bahmanrokh; Muhammad Misbah Muhamad Zulkimi; Nor Hapishah Abdullah; Muhammad Syazwan Mustaffa; Arlina Ali (2026)
Indexed by ERA